2008
DOI: 10.1007/s00396-008-1872-4
|View full text |Cite
|
Sign up to set email alerts
|

Drop profile analysis tensiometry with drop bulk exchange to study the sequential and simultaneous adsorption of a mixed β-casein /C12DMPO system

Abstract: The formation of mixed protein/surfactant adsorption layers is studied by the drop profile analysis tensiometry equipped with a special tool for drop volume exchange during experiments. This arrangement allows investigating in the traditional way by simultaneous adsorption from a mixed solution and also by a subsequent adsorption of the protein followed by surfactant. The experiments are performed for β-casein as the protein in the presence of different amounts of the non-ionic surfactant C 12 DMPO. The surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 36 publications
1
36
0
Order By: Relevance
“…3), and the measured decrease in the pressure after wash-off corresponds to an increase in the interfacial tension. Such an increase indicates that the molecules at the interface can desorb [52][53][54] :…”
Section: Pressure-area Isothermsmentioning
confidence: 99%
“…3), and the measured decrease in the pressure after wash-off corresponds to an increase in the interfacial tension. Such an increase indicates that the molecules at the interface can desorb [52][53][54] :…”
Section: Pressure-area Isothermsmentioning
confidence: 99%
“…Third, it is possible to follow the IFT while surface active species are being adsorbed/desorbed maintaining the drop/bubble volume constant [21][22][23] .…”
Section: Introductionmentioning
confidence: 99%
“…Such device was successfully validated and used to follow the desorption of a non-ionic surfactant (Triton X-100) and a series of n-alkyl dimethyl phosphine oxide surfactants by Ferri et al 18 . Similarly, Kotsmár et al 23 followed the desorption kinetics of a surfactant-protein complex (C 12 -dymethil phosphine oxide and βcasein) concluding that displacement by the formation of complex-like structures was the main cause of desorption.…”
Section: Introductionmentioning
confidence: 99%
“…The group of Reinhard Miller in Golm reported for the first time a direct comparison of the behaviour of adsorption layers formed by simultaneous and sequential adsorption in [43]. Since then, they have deepened into this aspect by reporting competitive and sequential adsorption of proteins (BCS, BLG and lysozime) and surfactants (ionic and non-ionic) at different interfaces, including interfacial rheology and theoretical considerations [1,3,11,13,41,[43][44][45]. In general, nonionic surfactants displace the proteins from the interface following an orogenic mechanism [42] and do not provide large differences between competitive and sequentially formed films.…”
Section: Proteins: Polysaccharides and Surfactantsmentioning
confidence: 99%
“…Namely, the replaced amount of mucin simultaneously is higher than that replaced sequentially, because the mucin-surfactant complex formed simultaneously is more surface active than the sequentially formed at the interface. Conversely, when the displacing surfactant is non-ionic, the authors found that sequential and simultaneous adsorption isotherms are identical [43]. This behaviour is attributed to different protein-surfactant interactions: hydrophobic type for non-ionic surfactants and combined hydrophobic/electrostatic for ionic surfactants.…”
Section: Proteins: Polysaccharides and Surfactantsmentioning
confidence: 99%